APLIKASI DAN PERSEPSI PENGGUNAAN TEKNOLOGI OLEH DOSEN PENGAJAR BAHASA INGGRIS DI UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Nine Febrie Novitasari (Relawan Jurnal Indonesia, 2018)
Technology has been widely used in educational field, including in higher education level. To cope with the developing era and the now students who are technology natives, lecturers need to use technology in everyday teaching and learning process. Being concerned with this, this current study was conducted to measure lecturers’ perception and use of technology in their teaching and learning process. The study was conducted qualitatively by delivering questionnaires to English lecturers at University of Abdurachman Saleh Situbondo. The results showed that the most frequent uses of technology were technology use by students in clasroom, technology use by lecturers when delivering materials, and the use of professional emails by lecturers. Besides, it was also found out that most lecturers felt positive towards the use of technology in their classroom. They used the technology confidently, and they integrated technology in their teaching and learning process using mainstream and instructional types of technology. This study is finally expected to give some insights for lecturers to be always updated with the development of technology and are aware with obstacles that might occur during the use of technology.